Urgensi Pengaturan Zakat: Evaluasi Zakat Sebagai Pengurang Pajak Penghasilan Terhutang ( Taxes-Credit ) dalam Undang-Undang Nomor 11 Tahun 2006 Tentang Pemerintahan Aceh - Fuadi, Fuadi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
Article 192 of Law No. 11 of 2006 on the government of Aceh states that "zakat as a reduction of income taxes payable (taxes credit)," while article 22 of Law No. 23 of 2011 on the management of zakat states that "zakat as a deduction the amount of taxable income (taxes deductable)." therefore there has been a disharmony of the two provisions, and so far the provisions of zakat as a reduction of income tax payable (taxes credit) in Aceh has not been effective yet. The purpose of this study is to investigate the implementation of the provisions of "zakat as a tax deduction payable in Aceh. and what regulation dispute resolution between Article 192 of Law No. 11 of 2006 on the Aceh government with the income tax law in Aceh." The results of the research indicates that the implementation of zakat as a reduction of income taxes payable have not been effective because the central government represented by the Ministry of finance rejected the provision. As for the solution is a) change/void the article such by the competent institutions that formed it; b)apply for a judicial review to the constitutional court; c) apply the principles of law /legal doctrine "lex specialis derogat legi generalis," The President issued the implementing regulations of Article 192 of Law No. 11 of 2006.